LOCAL CRAFT-MANSHIP AND WISDOM ON COMMUNITY HEALTH SYSTEM OF KHMER ETHNIC GROUPS IN SURIN PROVINCE,THAILAND AND SIEMREAP PROVINCE, CAMBODIA - Kaewla, Wasana (PEOPLE: International Journal of Social Sciences, 2017)
This research purposed attainment preparing materials, craftsmanship and compares the elements of craftsmanship in Community Health Systems ethnic Khmer Surin, Thailand and Cambodia. The Qualitative research, an Ethnocentric data was collected by interview,in-depth interviews and participant observation. The main key respondants were priests, novices, patients and care givers, patients’ relatives, Folk Philosophers Including a feminist local healer called Ma-Ma. An analyzed and synthesized and Conclusions was based on systematic thinking Decoding intellectual and interpretation of the (Claude levi-strauss.1986 and 1973).The study found that the handcrafts role in community health care system seem to focus on the cone bevel which tighten up from ground floor level. It is considered Supernatural but it is made of local materials under natural conditions. They use the trunk and leaves of banana trees coconut trees, jackfruit trees, the leaves of the Bodhi tree and Indian coral tree Blady grass and Artificial materials are used to make durable Parts, crumpled paper, colored paper foam and aged glossy paper.Artifacts that reflect the role of handicrafts in the health system including community health are called “GURU” The beveled layers indicate teachers and deities levels or layers. The ritual are indispensable and hold a central place which is adorned with marquee pillars called majority pillars stock. The Artifacts role of ceremony was basic psychological treatment in the community. Including things such as the nine Square tray, Betel nut blocks (a set of four bevel) prieces of Brahmanism and Buddhism worship.It is sometimes used as a birth worship set.Local craftsmanship wisdom in the community health system has inherited a rich cultural heritage because the preparation of the materials, and the ceremony combined with the traditional beliefs and worship are all part of the ceremony. Brahmanism and Buddhism respect the belief on faith is to be accepted. The cooperation for the purpose of the ritual is a part of the wisdom and has a significant role in the community. The co-operation for the purpose of the ritual for the community. The ritual has a significant role at the local level and is a part of the public health system, and should be upgraded as a service to the community.